Pengaruh Fasilitas, Lokasi dan Citra Destinasi terhadap Minat Berwisata pada Objek Wisata Danau Dua Rasa Labuan Cermin - Hadad Muzakki; Saida Zainurrosalamia (Yayasan Literasi Sains Indonesia, 2025)
Labuan Cermin's two-flavored lake tourism is one of Berau's secret gems that is quite attractive to locals and tourists alike. The current condition has problems that occur in facilities, location and destination image, so that it has an impact on tourist interest in visiting where the available facilities are still inadequate and accessibility is very far from urban areas, moreover there have been crocodiles entering the lake area so that this problem can affect tourist interest in visiting the tour. This study aims to determine the effect of facilities, location, and destination image on travel interest in the Labuan Cermin two-flavor lake tourist attraction. In this study, a quantitative method was used with a sample size of 80 tourists. The sampling method used is non probability sampling, namely purposive sampling. Data collection techniques with questionnaires that have been designed. The method used in this study is multiple regression analysis which is analyzed using SEM-PLS 3.0 software. The results showed that facilities had no effect on travel interest with a p-value of 0.850 > 0.05, while location and destination image had a positive effect on travel interest with a p-value of 0.017 and 0.000 < 0.05, respectively. The R-square test result of 0.741 shows that travel interest is influenced by facilities, location, and destination image by 74.1%, while the rest is influenced by other variables. Conclusion that the manager must provide adequate facilities, clear directions and promote tourist attractions to attract tourists to visit.